2020
DOI: 10.1016/j.medcli.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Impacto emocional de la pandemia de Covid-19 en los trabajadores sanitarios de uno de los focos de contagio más importantes de Europa

Abstract: Antecedentes y objetivo La actual pandemia de Covid-19 ha puesto a los profesionales sanitarios de todo el mundo ante un desafío sin precedentes. Esto les ha podido causar dificultades emocionales y problemas de salud mental. El objetivo del presente estudio fue analizar el estado emocional de los trabajadores del Hospital de Igualada (Barcelona), mientras se enfrentaban a uno de los focos de contagio más importantes de Europa. Pacientes y métodos Se incluyó a un total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 23 publications
3
17
0
15
Order By: Relevance
“…59 In our study, senior professionals (>55 years) reported lower rates of anxiety, depression, insomnia, and stress. This is consistent with other studies 60,61 that indicate that the protective effect of "being senior" is due to the fact that expertise and confidence helps minimize the stress caused unforeseen situations. 18 It should also be noted that the rate of infected HCWs (12.28%) is practically 3-4 times higher than elsewhere.…”
Section: Discussionsupporting
confidence: 92%
“…59 In our study, senior professionals (>55 years) reported lower rates of anxiety, depression, insomnia, and stress. This is consistent with other studies 60,61 that indicate that the protective effect of "being senior" is due to the fact that expertise and confidence helps minimize the stress caused unforeseen situations. 18 It should also be noted that the rate of infected HCWs (12.28%) is practically 3-4 times higher than elsewhere.…”
Section: Discussionsupporting
confidence: 92%
“…Their exhaustion increased as the pandemic progressed, causing them to lose the resilience skills they had developed during the first wave. Consequently, in the second wave, feelings of outrage emerged among professionals at the insincere acknowledgement of their work by managers and politicians and the lack of healthcare and health prevention plans for professionals on the part of organizations [43,47,63].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, the incidence of anxiety disorders, depression, and posttraumatic stress disorder increased considerably among ICU professionals during the pandemic [16,[32][33][34][35][36][37][38][39][40][41][42][43][44]. Professional quality of life has been undermined by an increase in burnout syndrome and compassion fatigue, especially among women and nurses [40,[45][46][47][48][49][50]. Regenold and Vindrola-Padros [51] argue that gender is significant when understanding the experiences of healthcare professionals during COVID-19 as it illuminates ingrained inequalities and asymmetrical power relations, with gendered organizational structures interacting to shape healthcare workers' experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the impact on the workforce's mental health became a priority during the first wave, and studies are already published. Most of them found significant differences in stress and anxiety symptoms by gender and job category (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Metaanalytic studies demonstrate that being a woman and lower-paid jobs, such as nursery, are risk factors for higher psychological distress during the pandemic (18-23).…”
Section: The Pandemic and The Medical Workforcementioning
confidence: 99%